Praktik Pembelajaran Terpadu pada Madrasah Berbasis Pesantren Modern di Sidoarjo - Najiyah, Siti Firqo; Prasetia, Senata Adi (Fahima, 2024)
This article explores the practice of integrated learning at a modern pesantren-based madrasa, i.e. Madrasah Aliyah Bilingual, Junwangi, Krian, Sidoarjo. Conventional teaching methods have been inadequate in providing enriching perspectives and enjoyable direct learning experiences. In contrast, integrated learning, which has become a trend in modern educational institutions, promotes a holistic and enjoyable learning experience. The article argues that integrated learning practices effectively help create a comprehensive cognitive framework for students, enabling them to understand and construct interrelated concepts. Through this modality, students are expected to develop the ability to identify, associate, evaluate, and meaningfully use available information. This article employs qualitative research based on field studies, with data analysis including data display, data condensation, and conclusion drawing. The findings reveal that the integrated learning practice at this madrasa implements two models simultaneously: the spider-web model and the integration model. Both models are effective and efficient in supporting the integrated learning process in a school within a pesantren culture.